Kung Fu Fighting: The Cultural Pedagogy of the Body in the Vovinam Overseas Vietnamese Martial Arts School - Carruthers, Ashley (The Australian journal of anthropology, 1998)
This paper explores the pedagogic practices by which Overseas Vietnamese elites seek to enlist the young in a shared conception of Vietnamese identity in the context of a martial arts organisation. It shows how the contradictory principles of gerontocratic and meritocratic social structuration, identified in the Vietnamese system of person reference, are given embodied form in the school's practice. The paper concludes with a reflection on how incorporation into this habitus and the relation to the Vietnamese body it offers may act as a defence, albeit an ambivalent one, against classifications of the Vietnamese body as abject emanating from the host society.